Fundamentals of silicon carbide technology : growth, characterization, devices and applications - Kimoto, Tsunenobu, 1963-; Cooper, James A., 1946- (Singapore : Wiley, 2014)
"Based on a number of breakthroughs in SiC material science and fabrication technology in the 1980s and 1990s, the first SiC Schottky barrier diodes (SBDs) were released as commercial products in 2001. The SiC SBD market has grown significantly since that time, and SBDs are now used in a variety of power systems, particularly switch-mode power supplies and motor controls. SiC power MOSFETs entered commercial production in 2011, providing rugged, high-efficiency switches for high-frequency power systems. In this wide-ranging book, the authors draw on their considerable experience to present both an introduction to SiC materials, devices, and applications and an in-depth reference for scientists and engineers working in this fast-moving field."--
""Chapter 10: Optimization and Comparison of Power Devices""""10.1 Blocking Voltage and Edge Terminations for SiC Power Devices""; ""10.2 Optimum Design of Unipolar Drift Regions""; ""10.3 Comparison of Device Performance""; ""References""; ""Chapter 11: Applications of Silicon Carbide Devices in Power Systems""; ""11.1 Introduction to Power Electronic Systems""; ""11.2 Basic Power Converter Circuits""; ""11.3 Power Electronics for Motor Drives""; ""11.4 Power Electronics for Renewable Energy""; ""11.5 Power Electronics for Switch-Mode Power Supplies""
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Silicon carbide; Semiconductors; Integrated circuits; Silicon carbide; TECHNOLOGY & ENGINEERING -- Mechanical; Integrated circuits; Semiconductors; Silicon carbide; Electronic books